The Idea of Religious Minorities and Social Cohesion in India’s Constitution: Reflections on the Indian Experience - Choudhary, Vikas K. (Religions, 2021)
India has many religious groups, of which Hindus are a majority, and Muslims, Christians, Sikhs, Buddhists and Jains are minorities. India’s Constitution, adopted in 1950, departed from the existing norms of secularism in Europe and elsewhere, which suggested a strict separation of religion and state. Moreover, freedom of religion is a Fundamental Right guaranteed under the Indian Constitution. With its distinct model of secularism and special provisions for religious minorities, India’s social cohesion arrangement needs special attention. On one hand, the distinct understanding of secularism in the Indian context has led to the advancement of religious pluralism. At the same time, it has invited criticism for selective intervention in the affairs of religious communities from governments in power. The selective intervention has challenged the exclusivity of Indian secularism. This article evaluates the constitutional and theoretical ideas underlying provisions on religious minorities and freedom of religion enshrined in the Indian Constitution. It appraises the idea of religious minorities enshrined in the constitution through a discussion of the process that shaped the idea. The article reflects on the Indian experience of managing the rights of religious minorities and freedom of religion. By analysing a landmark judgement related to freedom of religion and the rights of religious minorities, the article evaluates whether the Indian Constitution advances a model of social cohesion by balancing freedom of religion and the rights of religious minorities or remains ineffective in achieving the same.